Optimization Of Biogas Production From Poultry Manure Wastewater In 250 Ml Flasks - Choo, Wei Chun; Nina Farhana, Mohd Jamaludin; N., Zainol (Penerbit Universiti Teknologi Malaysia, 2015)
A research was conducted on anaerobic digestion from poultry manure wastewater to produce biogas. This research was considered as a triumph to the concept of waste-to-wealth. The poultry manure collected was characterized and pre-treated to remove excessive ammonia-N which caused inhibition to the biogas production. Central Composite Design (CCD) with five replicates at centre points was used to investigate the simultaneous effect of the variables: agitation (110-130 rpm) and reaction time (2-4 days) on the biogas production. Then, the experiment was designed and analyzed using Design Expert V7.0 software by applying response surface methodology (RSM) concept.The biogas production performance was evaluated on the basis of biogas yield from initial Chemical Oxygen Demand (COD) and was found ranged from 0.49 to 4.37 mL/g COD. Quadratic model was well fitted (R-squared>0.80) with a confidence level higher than 95 %. The optimum biogas production condition was at agitation: 120 rpm and reaction time: 3.3 days. Under this condition, 4.45 mL/g COD of biogas yield was obtained. This counted for 5.82% error from predicted values.